Sea otter conservation - Larson, Shawn E.; Bodkin, James L. (James Lee); VanBlaricom, G. R. (Glenn R.), 1949- (Amsterdam ; Boston : Academic Press, 2015)
Sea otters are good indicators of ocean health. In addition, they are a keystone species, offering a stabilizing effect on ecosystem, controlling sea urchin populations that would otherwise inflict damage to kelp forest ecosystems. The kelp forest ecosystem is crucial for marine organisms and contains coastal erosion. With the concerns about the imperiled status of sea otter populations in California, Aleutian Archipelago and coastal areas of Russia and Japan, the last several years have shown growth of interest culturally and politically in the status and preservation of sea otter populations. Sea Otter Conservation brings together the vast knowledge of well-respected leaders in the field, offering insight into the more than 100 years of conservation and research that have resulted in recovery from near extinction. This publication assesses the issues influencing prospects for continued conservation and recovery of the sea otter populations and provides insight into how to handle future global changes.
Includes bibliographical references and index.
Print version record.
Keywords: Sea otter -- Conservation; NATURE -- Animals -- Mammals; SCIENCE -- Life Sciences -- Zoology -- Mammals; Electronic books; Electronic books